Cultural Value in Mantra Menyapih in Village Communities: Literature Function Study - Marwanto Marwanto (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
In fact, the tradition of weaning spells is still developing and surviving to this day, the existence of this tradition is indeed needed by the community for their children to suckle their mothers. Stopping the child from sucking on his mother again is indeed quite difficult, so the people bring their children to suwuk experts, in this case dukun, kyai and local leaders. Suwuk expert will say rapalan or mantra in this case. The purpose of this study is to describe cultural values in the weaning mantra on rural communities: the study of literary functions. This study uses an observation method with ordinary observations because of observations carried out by researchers without being involved in direct contact with the actors (informants) who were the target of the research. The results of this study, people still use the services of expert suwuk in this case can dukun, suwuk experts, or traditional leaders, so that their children stop asking for milk.